The Effect of Transportation Supplier Performance, Loading and Unloading Performance, and Logistics Service Quality on Transportation Performance and Their Implications for the Operational Performance of Paket Pos Kilat Khusus at the Kendari Main Branch Office - Adam Nugroho; Melia Eka Listiani; Saptono Kusdanu Waskito (Dinasti International Journal of Education Management and Social Science, 2025)
This research analyzes the influence of transportation supplier performance, loading and unloading operations, and logistics service quality on transportation performance and their implications for operational performance of Special Express Parcel service at the Kendari Main Branch Office of PT Pos Indonesia. Using a quantitative approach with Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) via SmartPLS software, data were collected from 142 respondents across various operational units. The research reveals that transportation supplier performance has the strongest impact on transportation performance (β = 0.580), followed by loading and unloading performance (β=0.496) and logistics service quality (β=0.089). The model explains 98.4% of transportation performance variance, demonstrating exceptional predictive capability. All hypotheses were statistically significant (p<0.05), with t-statistics exceeding the critical value of 1.977. However, transportation performance explains only 5.5% of operational logistics performance variance, suggesting additional influencing factors. The findings indicate persistent operational challenges at KCU Kendari, including 100% delayed truck arrivals (averaging 30 minutes 26 seconds), 12.02% misrouting in loading and unloading operations, and 29.30% unresolved customer complaints. The research recommends implementing integrated supplier management systems, investing in automated handling equipment, strengthening customer service processes, and deploying advanced fleet management technologies to achieve sustainable operational improvements and maintain competitive advantage in Indonesia's dynamic logistics industry.